Scientific Writing: What Needs to Be Included - Dahal, Niroj (GS Spark: Journal of Applied Academic Discourse, 2025)
Scientific writing serves as the basis of academic communication and knowledge dissemination in research communities worldwide. This editorial examines the essential components that constitute effective scientific writing, addressing both structural and qualitative elements necessary for successful scholarly communication. The discussion encompasses fundamental aspects, including proper manuscript structure, adherence to formatting guidelines, ethical considerations, and the critical role of clarity in scientific expression. Drawing on established research methodologies and publication standards, this editorial guides researchers at all career stages who seek to enhance their scientific writing capabilities. Key areas explored include comprehensive the importance literature of reviews, methodological transparency, appropriate use of citations, and the ethical obligations inherent in scholarly publishing. The editorial emphasizes that effective scientific writing extends beyond merely documenting research findings to encompass clear communication of methodologies, implications, and limitations. Furthermore, it highlights the transformative potential of well-constructed scientific narratives in advancing interdisciplinary collaboration and fostering innovation across STEAM disciplines. The recommendations presented herein aim to support the development of writing practices that meet publication standards while also making significant contributions to the broader scientific discourse and advancing knowledge. Finally, this editorial concludes with a brief overview of the articles featured in Volume 3, Issue 1.